RESPIRATION PATHWAYS AND ECONOMIC ASPECT OF BARLEY (Hordeum vulgare). A REVIEW - Farhan Ahmad (Universitas Perjuangan Tasikmalaya, 2024)
Respiration is one of the most critical processes in the growth, development, and overall production of barley's iconic cereal crop (Hordeum vulgare L.). The complex molecular processes, complex regulatory systems, and ecological significance of barley respiration are all explored in this article. The analysis includes key data from the literature, covering topics such as metabolic pathways, water activity conditions, and regulatory elements affecting barley respiration. The study's objectives are gaining knowledge about barley respiration, understanding biochemical and molecular mechanisms, looking into regulatory pathways, emphasizing the value of agriculture, and identifying knowledge gaps. With a focus on providing insights for crop management, stress tolerance, supporting economic aspects, and sustainable agriculture in the face of global issues, this review seeks to advance our understanding of barley respiration and develop economical valuation. .